New oxford Social studies for pakistan grade 4 - Horsburgh, Nicholas (Karachi : Oxford university press, 2019)
New Oxford Social Studies for Pakistan Grade 4 is an educational textbook designed to help students deepen their understanding of the social studies concepts related to Pakistan, focusing on its geography, history, culture, and society. It builds on foundational knowledge from earlier grades and introduces more complex topics suitable for young learners.
Keywords: Social studies : textbook